Pengaruh Ketidakamanan Kerja terhadap Intensi Keluar dengan Komitmen Organisasional Sebagai Variabel Mediasi Pada Perawat Kontrakrumah Sakit Umum Citra BMC Padang - Raziq Fadillah Ezra; Syahrizal Syahrizal; Yuki Fitria (Universitas Negeri Padang, 2019)
The aim of this research is to analyze: (1) influence of Job Insecurity to Turnover Intention (2)Influence Job Insecurity to Organizational Commitment (3) Influence Job Insecurity to TurnoverIntention with Organizational Commitment as mediating variable. The population in thisresearch was all the contract nurses at General Hospital Citra BMC of Padang which amountedto 140 people. The sampling technique of this reserach is Cluster Propotional SamplingTechnique with total sample amounted 104 people. The data used are primary data andsecondary data. The data analysis technique used is multiple regression analysis with themediating variable with SPSS version 16.0 program. The result showed that (1) Job Insecurityhas positive and significant effect or Turnover Intention at contract nurse at General HospitalCitra BMC of Padang. (2) Job Insecurity has negative and significant effect on EmployeeEngagement at nurses of General Hospital of Padang (3) Organizational Commitment tomedicate the influence of Job Insecurity on Turnover Intention at contract nurses of GeneralHospital Citra BMC of Padang.Keywords: Turnover Intention, Job Insecurity, Organizational Commitment.Pendahuluan